Penerapan Strategi Directed Reading Thinking Activity untuk Meningkatkan Keterampilan Membaca Pemahaman Siswa Kelas III Sekolah Dasar - Neneng Sri Wulan; Hisny Fajrussalam; Nicken Ayu Triana (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This study was motivated by the low reading skills of third grade students when participating in Indonesian language learning activities. The research was conducted at SDN 6 Sindangkasih with 17 research subjects. The purpose of the research is to improve the process of learning activities, especially reading comprehension skills so that it can increase students' activities and reading comprehension skills by using the Directed Reading Thinking Activity strategy. The type of research used is classroom action research. The results showed an increase in teacher activities, student activities and students' reading comprehension skills. Based on the acquisition of the average learning outcomes of reading comprehension skills there was a pre-cycle of 61.75 with the number of students who completed learning amounted to 4 people and students who did not complete learning amounted to 13 people. Cycle I the average acquisition of students' reading comprehension skills was 71.47 with 11 students who were complete and 6 students who were not complete. In cycle II, the average acquisition of students' reading comprehension skills was 82.94 with 16 students who completed their learning and 1 student who did not complete their learning. With this, the application of the Directed Reading Thinking Activity learning strategy is proven to be able to improve learning activities during the learning process so that it can improve students' reading comprehension skills.